Editorial: Acknowledging complexity and heterogeneity in causality – implications of recent insights into neuropsychology of childhood disorders for clinical practice. (July 2014) - Coghill, David
<x xml:space="preserve">Abstract</x> From a clinical perspective research that tries to unravel the causal processes that underpin mental health problems can often seem esoteric and far removed from day to day clinical decision making. Indeed even though there are now a plethora of evidence based clinical guidelines that aim to support the translational process it still takes many years for new scientific understanding of a condition to permeate routine clinical practice, via this route. At the same time, however, a clinician's personal and informal interpretation of what is causing their patients' problems can have very important clinical implications and impact directly on; their formulation of a patient's presentation, the way in which they transmit this to the patient and their family and any treatment decisions that are made. Clinicians who are able to stay up to date with the latest evidence and scientific debate about what is and is not known about the underlying causes of mental health problems should be at an advantage in this regard. But for the busy clinician, 'just' staying up to date with the huge amount of new directly related to this topic is in itself a big ask in itself – critically appraising this evidence, in a balanced way, another thing altogether. To facilitate this process it is necessary for researchers to make every effort to include a balanced, clear and relevant discussion of the translational implications of their findings. In particular they must try to avoid overselling a message that may attract a lot of initial attention but that may, in time, prove to be a false dawn or an over simplification.